Antiglycation and antioxidant activity of herbal medicines used in the treatment of climacteric symptoms - Gomes, Amanda C. [UNESP]; Figueiredo, Célia C.M. [UNESP]; Martins, Gustavo R. [UNESP]; Granero, Filipe O. [UNESP]; Silva, Luciana P.; Gonçalves da Silva, Regildo M. [UNESP] (Elsevier, 2023)
Objectives: This work had the objective to evaluate the antiglycation and antioxidant potential of Cimicifuga racemosa L., Trifolium pratense L., Humulus lupulus L. and Morus nigra L., commonly used in traditional medicine for the treatment of climacteric symptoms. Methods: Antioxidant activity was evaluated by 2,2-Diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging, ferric reducing antioxidant power, inhibition of lipid peroxidation thiobarbituric acid reactive substances (TBARS), nitric oxide (NO) radical scavenging and inhibition of oxidative haemolysis test. The evaluation of antiglycation activity was performed by the determination of relative electrophoretic mobility of bovine serum albumin (BSA) with ribose and BSA with methylglyoxa in the presence and absence of Cu2+ ion. Total polyphenol and flavonoid contents were determined by spectrophotometric methods. Results: The highest antioxidant activity for DPPH and ferric reducing antioxidant power test was detected in Humulus lupulus (83.56% and 46.95 µM TE/g dry extract, respectively). For the inhibition of lipid peroxidation, the lowest percentages of TBARS were found in M. nigra (4.82%) and H. lupulus (18.26%). C. racemosa presented the lowest nitrite formation (34.57 µmol/mL nitrite formed) in nitric oxide test. T. pratense presented the highest polyphenol (24.61 mg GAE/g dry extract) and flavonoid (22.79 mg RE/g dry extract) contents. For the oxidative haemolysis assay, the extracts showed concentration-dependent inhibitory capacity, while for the antiglycation activity all extracts showed antiglycation potential against glycation of BSA promoted by Ribose evaluated by the electrophoretic profile. Conclusions: In view of the results obtained in this study, it was possible to verify that the dry extracts of herbal medicines used for climacteric symptoms present antioxidant and antiglycation activities, mainly due to the presence of phenols compounds in their composition.
Keywords: Aging; Herbal medicine; Menopause; Oxidative stress; Protein glycation